2018
DOI: 10.2174/0929867325666171226114838
|View full text |Cite
|
Sign up to set email alerts
|

Role of Redox Homeostasis and Inflammation in the Pathogenesis of Pulmonary Arterial Hypertension

Abstract: This review addresses pulmonary arterial hypertension (PAH), an incurable disease, which determines high morbidity and mortality. Definition of the disease, its characteristics, classification, and epidemiology are discussed. A difficulty in the diagnosis of PAH due to the lack of symptoms specificity is highlighted. Echocardiographic analysis and electrocardiogram of patients help in the diagnosis and in the follow up of the disease. Nevertheless, right ventricle (RV) catheterization constitutes the gold stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…26,27) Aside from the adverse effects of ROS, the upregulation of vascular NADPH oxidase evoked proliferation and apoptosis-resistance of the pulmonary arterial wall cells. 2) In this study, our data showed that the MDA level and NADPH oxidase expression were significantly increased in MCT-induced pulmonary hypertension rats, and AOS reduced the MCT-induced MDA production and NADPH oxidase expression. These results indicated that AOS protected pulmonary hypertension rats via the regulation of redox states.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…26,27) Aside from the adverse effects of ROS, the upregulation of vascular NADPH oxidase evoked proliferation and apoptosis-resistance of the pulmonary arterial wall cells. 2) In this study, our data showed that the MDA level and NADPH oxidase expression were significantly increased in MCT-induced pulmonary hypertension rats, and AOS reduced the MCT-induced MDA production and NADPH oxidase expression. These results indicated that AOS protected pulmonary hypertension rats via the regulation of redox states.…”
Section: Discussionsupporting
confidence: 49%
“…1) Current available therapies for PAH are limited, mostly either designed to depress vascular contractility or reduce pulmonary arterial resistance, such as calcium channels inhibitors, phosphodiesterase-5 inhibitors, prostacyclin analogues, soluble guanylate cyclase agonists, and inhaled nitric oxide. 2) However, these drugs fail to reverse the progression of PAH and improve the poor prognosis. Thus, more effective pharmacological interventions are urgently needed for the treatment of PAH.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress plays a key role in pulmonary vascular remodeling, which in turn increases the RV after-load leading to RV hypertrophy and eventual RV failure (Bello-Klein et al, 2018). Additionally, it has been shown that the RV is more vulnerable to oxidative stress than the LV (Reddy and Bernstein, 2015), potentially because the RV cannot upregulate manganese superoxide dismutase expression, an enzyme that combats ROS (Shults et al, 2018).…”
Section: Contribution Of Oxidative Stress To Rv Remodeling In Phmentioning
confidence: 99%
“…Earlier studies have recognized the role of inflammatory pathways activation as an important pathological event in the development of hypertension 3 . This growing evidence suggests that systemic inflammation endorses endothelial damage, which further contributes to physiological alterations in the endothelium 4 .…”
Section: Introductionmentioning
confidence: 99%